2008
DOI: 10.1002/hbm.20712
|View full text |Cite
|
Sign up to set email alerts
|

Is a preserved functional reserve a mechanism limiting clinical impairment in pediatric MS patients?

Abstract: We evaluated the functional magnetic resonance imaging (fMRI) correlates of simple movement performance in patients with pediatric multiple sclerosis (MS) and their relation with the extent of T2 lesion volume (LV), to improve our understanding of the mechanisms leading to their short/medium term favorable clinical course. We obtained fMRI during repetitive flexion-extension of the last four fingers of the right hand and brain dual-echo scans from 17 right-handed patients with pediatric relapsing-remitting MS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
37
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 35 publications
(42 reference statements)
5
37
0
1
Order By: Relevance
“…1,3 Recent volumetric MRI data have demonstrated that pediatric patients with MS have a smaller overall brain volume than would be expected for age, 13 in spite of the purported higher capability to compensate for brain damage, 14 suggesting that demyelinating lesions can also affect overall brain growth and development. It is also important to note that cognitive dysfunction occurs in about 1/3 of children and adolescents with MS.…”
mentioning
confidence: 99%
“…1,3 Recent volumetric MRI data have demonstrated that pediatric patients with MS have a smaller overall brain volume than would be expected for age, 13 in spite of the purported higher capability to compensate for brain damage, 14 suggesting that demyelinating lesions can also affect overall brain growth and development. It is also important to note that cognitive dysfunction occurs in about 1/3 of children and adolescents with MS.…”
mentioning
confidence: 99%
“…25 Using resting-state fMRI, Rocca et al 26 showed that patients with POMS as compared with controls demonstrated decreased functional connectivity (FC), mainly in posterior brain regions, suggesting an impaired maturation of large-scale brain connectivity. In addition, increased FC of the medial frontal gyrus (implicating the attention network) was also observed.…”
Section: Mri Correlates Of Cognitive Impairmentmentioning
confidence: 99%
“…Nevertheless, in spite of this severity, the brain of pediatric patients exibits an high capability to compensate the damage: this finding is supported by the possibility to partially reduce the extent of CD in the long-term, and by studies with functional and nonconventional MRI demonstrating an higher plasticity of the brain. It has been demonstrated that the activation of brain areas after a simple movement of the hand, that is progressively more widespread with progression of MS, is more restricted in pediatric compared to adult MS [59], indicating a relatively preserved functional organization of the brain; moreover the pattern of connectivity among brain areas is more efficient in children, compared to adults (see also Differential diagnosis: can clinical manifestations and ancillary investigations make the difference? section).…”
Section: Clinical Aspects: How Similar To Adult Ms?mentioning
confidence: 99%